ANTIHYPERTENSIVE EFFICACY OF VALSARTAN IN SMOKERS VERSUS NON-SMOKERS WITH ARTERIAL HYPERTENSION: THE FIRST RESULTS OF RUSSIAN MULTICENTER OPEN STUDY - V. I. Podzolkov; V. A. Bulatov; A. V. Vigdorchik (Рациональная фармакотерапия в кардиологии)
Aim. To study antihypertensive efficacy and safety of valsartan (Diovan, Novartis Pharma) as well as patient’s compliance to the mono- or combined valsartan based therapy in smoking vs non-smoking hypertensive patients.Material and methods. It was a prospective multicenter observation study. 114 doctors from 81 medical institutions of Russia participated in the study. 650 hypertensive patients (41,2% of smokers and 58,8% of non-smokers; age 53,9±0,4 y.o. in average) were included in the study. The evaluation of therapy efficacy was based on analysis of systolic (SBP) and diastolic (DBP) blood pressure (BP) changes and of patient number who answered to the treatment and reached BP target level. Safety and compliance of the treatment also was analyzed. The initial valsartan dose was 80 mg OD and may be increased (up to 320 mg OD) by doctor for achievement of BP target level. A combination of the valsartan with hydrochlorothiazide was also allowed. Amlodipine (5-10 mg/d) or any other antihypertensive also may be added if necessary.Results. Significant decrease of SBP and DBP was observed in each group between the 1st and 5th visits. SBP decreased by 37,5 mm Hg (р<0,01) in smoking patients and by 37,6 mm Hg (р<0,01) in non-smoking ones. DBP decreased by 18,5 mm Hg (р<0,01) in smoking patients and by 15,9 mm Hg (р<0,01) in non-smoking ones. Differences in SBP and DBP changes were not significant between groups. Target BP level (<140/90 mm Hg) was reached in 96,2% of smokers and in 96% of non-smokers. 99% of smoking patients and 96,1% of non-smoking ones responded to valsartan based therapy according to defined criteria.Conclusion. Similar antihypertensive efficacy and safety of valsartan mono- and combined therapy was found out in smoking and non-smoking hypertensive patients.